(untitled) (Hematology Meeting Reports, 2009)
Chronic lymphocytic leukemia (CLL) is a disorder characterized by a progressive accumulation of mature B lymphocytes which either avoid death because of external survival signals or go into apoptosis to be replenished by proliferating precursors. CLL is the most common type of leukemia of elderly people in the Western countries.1 Although the median survival is around 10 years, in individual patients the prognosis is extremely variable, ranging from a very short to a normal life span. After decades during which the wait and watch management has been the normal approach to these patients, the attitude of the physicians towards CLL patients has changed remarkably during the last few years. The reasons for this change are manifold and some are discussed below.